Development of the E-Module on the History of the Entry of Islam in Pekalongan Regency Based on Project-Based Learning on Learning Interests of Class X IPS Students SMAN 1 Kedungwuni - Hakim, M Farid; Sunarjan, YYFR. (Indonesian Journal of History Education, 2016)
This study uses research and development models with descriptive quantitative analysis to describe the findings of research data. The objectives of this research are: (1) Know the stages of development of e-modules of historical learning; (2) Know the use of e-modules, and; (3) Increase the interest in learning grade X IPS 4 in SMAN 1 Kedungwuni through the use of e-module based on the local history of Islamic entry in Pekalongan Regency. The research used addie development models n-gain test analysis and linear regression. The results showed; (1) Based on the validity test of the e-module indicates that the e-module is qualified to be used as a learning resource; (2) Based on the n–gain test analysis of the pretest and posttest values obtained a figure of 0.79; (3) The development of e-modules affects the interest in learning the history of grade X IPS 4 students by 22.7% with a positive influence direction based on simple linear regression analysis.